Breizacanthus aznari sp. n. (Acanthocephala: Arhythmacanthidae) from the banded cusk-eel Raneya brasiliensis (Ophidiiformes: Ophidiidae) from the Patagonian coast in Argentina - Hernández-Orts, Jesús Servando; Alama-Bermejo, Gema; Alberto Crespo, Enrique; Anibal García, Néstor; Antonio Raga, Juan; Esteban Montero, Francisco (Folia parasitologica, 2012)
Breizacanthus aznari sp. n. is described from the banded cusk-eel Raneya brasiliensis (Kaup) (Ophidiiformes: Ophidiidae) from the Patagonian coast in Argentina. Breizacanthus Golvan, 1969 is currently composed of five species (including the new species) and is characterised by the absence of trunk spines; a short cylindrical proboscis with two types of hooks and lemnisci longer than the proboscis receptacle. Breizacanthus aznari is clearly distinguished from B. chabaudi Golvan, 1969 by having 12 longitudinal rows of hooks on the proboscis, instead of 16-18. The new species resembles B. golvani Gaevskaya et Shukhgalter, 1984, B. irenae Golvan, 1969, and B. ligur Paggi, Orecchia et Della Seta, 1975, all possessing 12 longitudinal rows of hooks. However, B. aznari differs from B. golvani in having 4-5 large hooks per row (vs. 8-9) and larger eggs. The new species can be distinguished from B. irenae by the shorter body size of females, the different range of numbers of large hooks of males (4-5 and 5-6, respectively), the smaller maximum number of small hooks of females (3 and 4, respectively), and the shorter lemnisci. Breizacanthus aznari differs from B. ligur by the smaller body length of females, the smaller maximum body length of males, the different range of numbers of large hooks of males (4-5 and 5-6, respectively), and smaller lemnisci. This is the first record of a species of Breizacanthus from fishes of the order Ophidiiformes and from the Southern Hemisphere. Comparative data on species of Euzetacanthus Golvan et Houlin, 1964 and Breizacanthus are also provided.
Keywords: Argentina; Animals; Atlantský oceán; Helminthiasis, Animal; nemoci ryb; Female; zvířata; mužské pohlaví; Fish Diseases; Fishes; Male; Atlantic Ocean; helmintózy zvířat; ženské pohlaví; Acanthocephala; ryby